Religious references in political campaigning: a comparative analysis of Latin America and Western Europe on social media - Schwörer, Jakob (Frontiers in Political Science, 2024)
The relationship between religion and politics is receiving increasing attention in political science, although the focus is often on voter attitudes. Despite secularization trends, scholars expect a resurgence of religion in Western European party politics, where Christianity as a native identity is opposed to non-native Islam by populist radical right parties. In this context, it is primarily hostility toward other religious groups that structures religious elements in political communication. In most Latin American societies, religiosity plays a much greater role for individuals, which is reflected in the discourses of political elites who use genuine religious references to appeal to religious voters (“sacralization of politics”). Using data from my own recent research on content analysis of parties’ and candidates’ Facebook profiles, this article compares how political actors in Latin America and Western Europe use religious references in electoral campaigns and how salient these discourses are. The results help to explain the different prominence of religious discourses in different democratic regions and religious markets. The article contributes to the ongoing debate on the role of religion in 21st century politics.